Estudo comparativo da analgesia preemptiva do tramadol combinado a dexametasona e diclofenaco de sódio em cirurgia de terceiro molar - Santos, Jadson Alípio Santana de Sousa (2011)
The aim of the present randomized, double-blind clinical trial was to investigate the effect of preemptive analgesia through a combination of tramadol+dexamethasone and tramadol+diclofenac sodium. Thirty patients were submitted to surgery for the bilateral removal of impacted lower third molars, with one side operated at a time. The first surgery was performed on one side with the preemptive oral administration of a single tablet of either tramadol+dexamethasone or tramadol+diclofenac sodium. The opposite side was operated a week later using the other drug combination. Anthropometric measurements and maximal mouth opening were determined in both the preoperative and postoperative period to assess the degree of swelling and trismus, respectively. As a rescue drug, the patients were permitted to use acetaminophen when needed to control postoperative pain. The patients were given a chart with a visual analog scale (VAS) to record postoperative pain and rescue drug intake. No statistically significant difference was detected with regard to pain intensity between the drug combinations (p = 0.08). Pain scores were lower with the tramadol+dexamethasone combination in comparison to the tramadol+diclofenac sodium combinations at the different evaluation times. With both protocols, mean VAS values were below 50 mm, representing moderate pain. With regard to trismus, the tramadol+dexamethasone combination allowed significantly greater postoperative mouth opening (p < 0.01). The tramadol+dexamethasone combination also demonstrated a significantly lesser degree of swelling, specifically for the measurements from the angle of the mandible to the ala of nose (p = 0.001), labial commissure (p < 0.001) and mentus (p < 0.001). No significant differences between the drug combinations were found regarding pain in the postoperative period following third molar surgery, as mild to moderate pain was reported using both protocols (determined by VAS values). With regard to inflammation, the tramadol+dexamethasone proved more effective than tramadol+diclofenac sodium, with statistically significant differences with regard to the degree of swelling and trismus.